El reconocimiento de los certificados de emisiones reducidas (CER) como un activo intangible (2012)
Global conferences to control climate change, such as the Kyoto Conference, have introduced a series of economic instruments that enable organizations to convert the savings of greenhouse gas emissions into potential income sources and funding for them. In Colombia, many companies have joined this market, but there is still great confusion about the accounting treatment of such income. This paper makes an exploration of the dynamics of emission certificates and their accounting treatment within the current regulatory framework in Colombia.